Daʿwah : A Contextual Islamic Sociological Jurisprudence Approach in Religious Court - Ahmad Muhammad Mustain Nasoha; Raihan Annaas Mubaarok; Muhammad Jundy Akbar; Ayatullah Tadzikri; Ilham Fajar Setiawan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the dynamics of divorce cases and child custody disputes in the Religious Court through a Contextual Islamic Sociological Jurisprudence approach, positioning family daʿwah as an instrument of socio-legal transformation. The study aims to analyze how Islamic law is not only applied in a normative-juridical manner, but also understood within complex social realities—particularly in the context of family conflicts. A qualitative method with a juridical-sociological approach is employed, encompassing analysis of court decisions, interviews, and literature review. The novelty of this research lies in the integration of the Islamic legal sociology approach with the concept of family daʿwah in the dispute resolution process, areas that have previously been treated separately. The findings indicate that a contextual approach can yield more humane and equitable solutions, particularly in determining child custody by accounting for psychological, social, and Islamic values. Furthermore, family daʿwah plays a strategic role as both a preventive and curative medium in minimizing conflict and strengthening family resilience after divorce. This study therefore proposes a new model for religious court practice that is more adaptive to the social realities of modern society